Cortical laminar necrosis triggered by hepatic encephalopathy and post-traumatic subarachnoid hemorrhage: Case report - Inas AL CHARE; Mickaël BONNAN (Radiology Case Reports)
Hepatic encephalopathy may trigger cortical laminar necrosis (CLN), which is characterized by diffuse symmetric cortical lesions. We report a 56-year-old woman with liver cirrhosis who presented with prolonged floor station, reduced alertness and left hemiplegia. Blood ammonia level was elevated. Magnetic resonance imaging showed acute left cerebellar infarction, diffuse cortical lesions mostly involving the right temporo-fronto-parietal cortex with restricted diffusion, and right subarachnoid hemorrhage. This case of CLN lesions related to hepatic encephalopathy is characterized by unique pattern of almost unilateral lesions. We hypothesize that the right predominance of the brain cortical lesions could be a consequence of synergistic factors associating subarachnoid hemorrhage in the setting of hepatic encephalopathy. This finding refines the pathophysiology of metabolic CLN.